Indonesian Muslim Intelligentsia and Power: By Yudi Latif (Singapore: Institute of Southeast Asian Studies, 2008. 544 pages.) (American Journal of Islam and Society, 2010)
Yudi Latif’s Indonesian Muslim Intelligentsia and Power provides a broad,interdisciplinary, and long-term study of Indonesia’s Muslim intelligentsiafrom the late nineteenth until the early twenty-first century. His methodologystresses the reinterpretation of secondary sources, but does include primarydata collected via a documentary and database survey, interviews, aquestionnaire, and direct observation. Latif attempts to situate his multigenerationaldescription and analysis within an interdisciplinary frameworkthat includes politics, economics, education, discursive practices, the publicsphere, and intellectual traditions. The book consists of seven chapters,including an introduction and a conclusion ...